PLAGIARISM, ITS ESSENCE AND MEASURES TO PREVENT AND HANDLE IT - V. I. LEVIN (Высшее образование в России)
The paper focuses on the essence of plagiarism as a phenomenon accompanying publication of the results of scientific research. The author dwells on the most dangerous consequences of plagiarism for science and society – from clogging up science by ignoramuses imitating scientific activity to the complete destruction of scientific institutions of the country. The paper gives a brief scientific report on the origin and development of the phenomenon of plagiarism and a review of publications related. It is a well-known fact that with the advent of digital technologies and online publishing plagiarism began to flourish. Nowadays the number of publications with different types of plagiarism used is comparable with the number of reliable papers and monographs. This situation is absolutely abnormal and it is aggravated by the fact that scholarly reputation is no more meaningful in today’s Russia. As a result, we have a growing population of officials with academic degrees and titles but with no reference to science. In such conditions, the country has no chances to develop and survive. Therefore, to prevent the expansion of plagiarism and to avoid scientific misconduct it is necessary to take measures including the following steps: 1) to hold regular lectures for students, postgraduates, doctoral students and young researchers on the topic of the history, guidelines, and ethical standards of research work, 2) to organize special services under scientific and academic institutions that will control researchers’ publication activity in order to detect possible plagiarism, 3) persons and institutions with the detected plagiarism, inappropriate authorship, and research manipulations are subject to public punishment. These steps do not demand any charges and state interference but will promote recovery of academic environment.